2021
DOI: 10.1002/acr.24407
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Capacity of High‐Density Lipoprotein Cholesterol Efflux Between Patients With Systemic Lupus Erythematosus and Rheumatoid Arthritis

Abstract: Objective Cholesterol efflux capacity (CEC) is the ability of high‐density lipoprotein (HDL) cholesterol to accept cholesterol from macrophages. Lipid profiles and CEC appear to be altered in patients with systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) due to disease activity and inflammation. CEC has been linked to cardiovascular events in the general population and to subclinical atherosclerosis in SLE and RA patients. The aim of this study was to establish whether CEC varies between patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…HDL CEC impairment has been reported in various rheumatologic autoimmune diseases, such as RA and systemic lupus erythematosus (SLE) [ 190 , 191 , 192 , 193 , 194 ]. In SLE, HDL CEC was inversely related to subclinical carotid atherosclerosis [ 195 ].…”
Section: Hdl Cec In Specific Conditionsmentioning
confidence: 99%
“…HDL CEC impairment has been reported in various rheumatologic autoimmune diseases, such as RA and systemic lupus erythematosus (SLE) [ 190 , 191 , 192 , 193 , 194 ]. In SLE, HDL CEC was inversely related to subclinical carotid atherosclerosis [ 195 ].…”
Section: Hdl Cec In Specific Conditionsmentioning
confidence: 99%
“…Decreased CEC has been linked to cardiovascular events in the general population [64,65]. A 2020 study that compared CEC in two autoimmune rheumatic diseases, SLE and rheumatoid arthritis found CEC to be more impaired in SLE [66]. Another cross-sectional study that included 195 SLE patients and 223 controls also found CEC to be compromised in SLE (P = 0.004).…”
Section: Sle Plasma Induces Changes In Cholesterol Handlingmentioning
confidence: 99%
“…Although SLE was under control in most patients, CEC in patients was lower compared to controls. In a recent study by our group [26], CEC was impaired in SLE patients independently of other in ammation-related lipid pro le modi cations that occurred during the disease. Moreover, CEC was associated with carotid plaques in SLE patients.…”
Section: Discussionmentioning
confidence: 80%